The structure of practical knowledge utilized for group tactics in ball games: An examination of pick and roll in basketball - Matsumoto, S.; Aida, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
This study was conducted to clarify the group tactical structures of "pick and roll" in basketball by having players who excel at the tactic share their knowledge verbally. It was anticipated that such sharing would help provide information useful for improvement of individual tactical skills in situations where multiple players face off on the court. To better understand this tactic, 8 female basketball players who compete at international level were interviewed regarding pick play, and their narratives were analyzed qualitatively. Our findings were as follows. In pick and roll, there is a "pause" between the offense and defense players before the screen is set, and a struggle for the angle at which the screen is set between the uninvolved players. Moreover, a conflict over whether or not to "bring it to 2-on-2" was interpreted as occurring during the screen set, while the struggle over whether to "reasonably advance the numerical advantage" was interpreted as occurring after the screen set. Top players make sense of 1-on-1 situations visually, but when they have to face 2 opponents, they use visual, auditory, and tactile sense to grasp the situation. Top players were also shown to have both the practical ability to directly implement their procedural knowledge, and the ability to fine-tune their play in terms of space and timing to better apply their skills to the game.